Listeria monocytogenes: Pathogenesis and Host Response - Goldfine, Howard; Shen, Hao.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
This comprehensive volume, written by experts in the field, includes concise and timely reviews of Listeria monocytogenes, one of the most intensively studied bacterial pathogens. Listeria monocytogenes is the cause of listeriosis, a potentially fatal disease that arises from the consumption of contaminated food. During the past two decades, studies of this organism have uncovered a wealth of information on its virulence factors, its genome organization, and its interactions with host cells and the immune system. This book serves as an important information source for those who are already working in the field, those who teach about infectious agents and those who are beginning to study this and related bacterial pathogens.
A 20-Year Perspective on Listeria monocytogenes Pathogenesis -- Listeriosis -- Listeria Genomics -- Metabolism and Physiology of Listeria monocytogenes -- The Cell Wall of Listeria monocytogenes and its Role in Pathogenicity -- Environmental Reservoir and Transmission into the Mammalian Host -- Regulation of Listeria monocytogenes Virulence Genes -- Invasion of Host Cells by Listeria monocytogenes -- Escape of Listeria monocytogenes from a Vacuole -- Actin-Based Motility and Cell-to-Cell Spread of Listeria monocytogenes -- Adaptive Immunity to Listeria monocytogenes -- Immune Evasion and Modulation by Listeria monocytogenes -- Bacteriophages of Listeria.
Keywords: Microbiology; Immunology; Bacteriology; Cell biology; Veterinary medicine; Food—Biotechnology.; Microbiology; Immunology; Bacteriology; Cell Biology; Veterinary Medicine/Veterinary Science; Food Science